A roadmap to achieve the global methane pledge. (1st March 2023) - Malley, Christopher S; Borgford-Parnell, Nathan; Haeussling, Seraphine; Howard, Ioli C; Lefèvre, Elsa N; Kuylenstierna, Johan C I
Abstract: The Global Methane Pledge (GMP), launched in 2021 and signed by 149 countries and the European Union, aims to reduce global anthropogenic methane emissions by 30% in 2030 compared to 2020 levels. However, the GMP does not specify the contribution of countries or methane-emitting sectors (fossil fuel production, agriculture and waste) to achieve this global goal. Nationally determined contributions (NDCs) describe countries' climate change commitments, and 86% of countries include methane within the scope of these targets. This paper aims to assess whether a roadmap (i.e. a set of mitigation actions) to achieve the GMP can be developed from those methane-targeted mitigation actions included within NDCs. The 476 methane-focussed mitigation actions within the 168 NDCs analysed are targeted in countries and sectors emitting approximately 40% of global methane. These mitigation actions are not specified in NDCs with implementation targets and timelines that are currently collectively sufficient to achieve the GMP goal. However, if all 476 mitigation actions are implemented to their maximum technical mitigation potential, their implementation could reduce global emissions by ∼31%. Therefore, mitigation actions in NDCs could achieve the GMP goal, but only if implemented to their fullest possible extent. There are also multiple opportunities to increase methane mitigation ambition further. Additional commitments to implement technical methane mitigation measures could lead to mitigation in excess of the GMP goal. Behavioural measures, such as dietary shifts and reduction in waste generation could further reduce methane, and are included in few NDCs currently.